SOCIALISERING PROCESS HUKUM PERBURUHAN DALAM ASPEK KEBIJAKAN PENGUPAHAN - Mr. Saprudin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2012)
The government’s intervention in wage policies started during the Old Order era with the enactment of Act Number 33 of 1947 on Accidents. During the New Order era the government expanded its intervention in wage policies by taking into effect Government Regulation Number 8 of 1981 on Wage Protection. Subsequently, during the Reformation era the government imposed further limitations to the administration of rules Private Law in matters of wage. As an impact of the socialisering process undertaken from period to period, the government has established various laws on wages intended to provide legal protection to workers. In other words, throughout those periods there has been a significant progress in terms of legal protection to workers in matters of wages. Campur tangan pemerintah di bidang pengupahan diawali pada era Orde Lama, yakni pada saat diundangkannya Undang-Undang Nomor 33 Tahun 1947 tentang Kecelakaan. Di era Orde Baru, peran pemerintah di bidang pengupahan semakin besar yaitu dengan ditetapkannya Peraturan Pemerintah Nomor 8 Tahun 1981 tentang Perlindungan Upah. Selanjutnya, di era reformasi pemerintah semakin membatasi ketentuan-ketentuan yang bersifat Hukum Privat di bidang pengupahan. Akibat socialisering process ialah di setiap periodisasi pemerintah telah menetapkan berbagai peraturan perundang-undangan di bidang pengupahan yang bertujuan untuk memberikan perlindungan hukum bagi pekerja/buruh. Dengan kata lain, di setiap periodisasi tersebut telah terjadi upaya peningkatan perlindungan hukum bagi pekerja/ buruh di bidang pengupahan.